Dry distillery grains with solubles in the meat feed - Aguilera Tigre, Mery Lizeth (2016)
One hundred day old Cobb 500 chickens of both sexes were used in a feed trial with the following treatments: T1, control diet; T2, diet with 5% of DDGS-maize; T3, diet with 10% of DDGS-maize; T4, diet with 15% of DDGS-maize; With the purpose of determining the effect on food consumption, live weight gain, feed conversion, economic merit and carcass weight and performance. The test was conducted under the conditions of a completely random design. Feeding was ad libitum and the trial had a duration of 42 days. The presence of DDGS-corn caused a small but consistent increase in food consumption as the proportion of the product increased; The highest increases in the first 14 days of age were achieved with 5% of the product, from 15 to 28 days with 10% of the product, at the same time, with 10% of DDGS-maize. Finished the control exceeded the treatments with DDGS. Likewise, with 10%, the food conversion was achieved closer to that of the control and the economic merit was slightly better, because it allowed to replace part of the soybean cake that is Considerably more expensive; The best carcass weight and yield was achieved with 10% DDGS in the diet.